Health Literacy and the Digital Divide Among Older Americans - Levy, Helen (J Gen Intern Med, 2014)
BACKGROUND: Among the requirements for meaningful use of electronic medical records (EMRs) is that patients must be able to interact online with information from their records. However, many older Americans may be unprepared to do this, particularly those with low levels of health literacy. OBJECTIVE: The purpose of the study was to quantify the relationship between health literacy and use of the Internet for obtaining health information among Americans aged 65 and older. DESIGN: We performed retrospective analysis of 2009 and 2010 data from the Health and Retirement Study, a longitudinal survey of a nationally representative sample of older Americans. PARTICIPANTS: Subjects were community-dwelling adults aged 65 years and older (824 individuals in the general population and 1,584 Internet users). MAIN MEASURES: Our analysis included measures of regular use of the Internet for any purpose and use of the Internet to obtain health or medical information; health literacy was measured using the Rapid Estimate of Adult Literacy in Medicine–Revised (REALM-R) and self-reported confidence filling out medical forms. KEY RESULTS: Only 9.7 % of elderly individuals with low health literacy used the Internet to obtain health information, compared with 31.9 % of those with adequate health literacy. This gradient persisted after controlling for sociodemographic characteristics, health status, and general cognitive ability. The gradient arose both because individuals with low health literacy were less likely to use the Internet at all (OR = 0.36 [95 % CI 0.24 to 0.54]) and because, among those who did use the Internet, individuals with low health literacy were less likely to use it to get health or medical information (OR = 0.60 [95 % CI 0.47 to 0.77]). CONCLUSION: Low health literacy is associated with significantly less use of the Internet for health information among Americans aged 65 and older. Web-based health interventions targeting older adults must address barriers to substantive use by individuals with low health literacy, or risk exacerbating the digital divide.